2015
DOI: 10.1080/10426507.2015.1073283
|View full text |Cite
|
Sign up to set email alerts
|

Condensation of 2-Ethoxyvinylphosphonic Acid Dichloroanhydride with 2,3,5-Trimethylphenol. Novel Method for Preparation of Phosphacoumarins

Abstract: The condensation of 2-ethoxyvinylphosphonic acid dichloroanhydride with 2,3,5-trimethylphenol in toluene in the presence of trifluoroacetic acid gives novel compounds of a 2-hydroxo-2-oxabenzo[е]-1,2-oxaphosphorinine series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…The structure of the obtained compound was confirmed by X-ray analysis (see the Supporting Materials for the detailed X-ray data). Presumably, the compound 3 is formed via an intermediate phosphaflavanoid, which further undergoes intramolecular cyclisation to give the final product, as was described by us earlier [ 42 ].…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The structure of the obtained compound was confirmed by X-ray analysis (see the Supporting Materials for the detailed X-ray data). Presumably, the compound 3 is formed via an intermediate phosphaflavanoid, which further undergoes intramolecular cyclisation to give the final product, as was described by us earlier [ 42 ].…”
Section: Resultsmentioning
confidence: 86%
“…Commercially available reagents were used without additional purification. The compound 2-Hydroxybenzo[ e ][1,2]oxaphosphinine 2-oxide 1 was obtained by the previously reported procedure [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the possible explanations for the observed reaction course was the formation of the halogenide of oxaphosphorine as the main intermediate in the synthesis of the macrocycles and the corresponding oxaphosphorine 64a was formed as a result of a parallel interaction. Therefore, a modified procedure was published in 2015 representing [77] a condensation method for preparation only of 1,2-oxaphosphorines 64c and 65b , c in toluene as a solvent media under reflux in yields of 75–85%.…”
Section: Synthesis and Some Reactions Of Alkyl 12-benzoxaphosphormentioning
confidence: 99%
“…However, reliable synthetic methods for phosphacoumarins are still limited to date. Traditionally, phosphacoumarins are mainly obtained from the intermolecular reaction of suitable starting materials or from predesigned complex phosphorus precursors via intramolecular functionalization . Chen and Rodios’ groups have employed salicylaldehydes and phosphonoacetates for the preparation of phosphacoumarins via the Knoevenagel reaction, which afforded only low yields (<21%) followed by the formation of phosphonocoumarins (Scheme a). , Fu’s group reported that the intramolecular condensation of 2-methoxycarbonylbenzylphosphonates delivered a diverse series of 4- O -substituted phosphacoumarins, which suffer from the requirement of multistep reactions to prepare the precursors (Scheme b) .…”
mentioning
confidence: 99%